DISTRIBUTION OF HEAVY METALS, SOIL MICROBIAL ENZYMES AND THEIR RELATIONSHIP IN KANO, NORTHWESTERN NIGERIA - Mohammed, Mansur Abdul; Olowolafe, Emmanuel Adewale (UI Scholars Hub, 2020)
The increase in population and industrial growth has led to increased production of industrial and domestic waste which contain heavy metals in various forms. Therefore, affect the diversity and activities of soil microbes and subsequently affect environmental sustainability. This research aimed at assessing the distribution of heavy metals, soil enzymes, and evaluate the functional relationship if any. The study area was divided into two locations as contaminated and control; thus, each location one square kilometre was demarcated and divided into 25 small square (grid). A Sample was collected in each grid from 0 – 15 cm depth using point composite sampling technique. The properties investigated are heavy metals, enzymes, pH, and soil temperature. The results of the analyses were subjected to statistical analyses to undertake one-way analysis of variance, and a t-test of means at value of <0.05, also correlation, and regression at a P<0.05 significant level. The results revealed that there is a gradual accumulation of all heavy metals and the concentration is higher in the contaminated than control locations. The soil is potentially polluted with Cd is clean from Cr, Fe, Mn, Zn, Pb, and Cu. High values of heavy metals were discovered in the dry season than the wet season due to rainfall which enhanced the dissolution, leaching, and runoff of heavy metals which is capable of removing the metals from the subsurface. High pH and temperature in the contaminated location influenced the toxicity and microbial activity respectively, this results in high enzymatic activity in the contaminated location. Favourable environmental conditions in the wet season led to the higher activity of the enzymes than the dry season. The finding also revealed that phosphatase and urease were negatively correlated with Cd and Ni. Inversely, dehydrogenase was negatively correlated with Ni and Zn. It was concluded that the determination of the heavy metals and enzymes reflects the microbial activities in soils and is considered as soil quality indicators.